Adverse events following HPV vaccination: 11 years of surveillance in Australia. Issue 38 (27th August 2020) - Phillips, Anastasia; Hickie, Megan; Totterdell, James; Brotherton, Julia; Dey, Aditi; Hill, Richard; Snelling, Tom; Macartney, Kristine
Highlights: Australian surveillance data for quadrivalent human papillomavirus vaccine over 11 years. Analysis, including a period of enhanced surveillance, affirms safety profile of the vaccine. During enhanced surveillance, syncope occurred at a higher rate in younger adolescents. This highlights the need for management protocols to prevent syncope-related injury. Other adverse events of special interest were reported rarely, consistent with other studies. Abstract: Background: Australia was the first country to implement a fully funded vaccination program with quadrivalent human papillomavirus vaccine (4vHPV) in 2007, including males from 2013. We examined adverse events (AE) following vaccination with 4vHPV from 11 years of post-marketing data, focusing on a period of enhanced surveillance and adverse events of special interest (AESI). Methods: AE following 4vHPV doses administered between April 2007 and December 2017 reported to Australia's national regulator, the Therapeutic Goods Administration, were examined; reports collected during enhanced surveillance in 2013 and 2014 were analyzed separately. Age and sex-specific rates, using denominator data from the national HPV vaccination register, were determined. Pre-specified AESI were identified using Medical Dictionary for Regulatory Activities (MedDRA®) Preferred Terms and examined in detail. Findings: Following nine million doses of 4vHPV vaccine administered in Australia, 4551 AE reports were identified. The crude reporting rate was 39.8 per 100 000 doses in the funded cohorts, excluding the enhanced surveillance period. The reported rate of syncope in 12 to 13-year-old males and females was 29.6 per 100 000 doses during enhanced surveillance and 7.1 per 100 000 doses during the remaining study period; rates of syncope were higher in younger compared to older adolescents. The rate of anaphylaxis (0.32 per 100 000 doses) was consistent with published rates. Other AESI including autoimmune disease, postural orthostatic tachycardia syndrome, primary ovarian insufficiency, Guillain-Barré syndrome, complex regional pain syndrome and venous thromboembolism, were reported at low rates and analysis did not reveal unexpected patterns that would suggest causal association. Interpretation: AESI, apart from syncope, were reported rarely. The higher rate of syncope among younger adolescents highlights the need for management protocols to prevent syncope-related injury. Analysis of this large, longitudinal dataset in a country with high vaccine uptake, including a period of enhanced surveillance, affirms the safety profile of 4vHPV.